Does neighborhood walkability affect ethnic diversity in Berlin? Insights from a spatial modeling approach - Alexandros BARTZOKAS-TSIOMPRAS; Yorgos N. PHOTIS (European Journal of Geography)
Prior research has reported that people living in more walkable places gain significant health, and environmental sustainability benefits. However, the positive impacts of walkable urbanism are not often inclusive and might affect minority groups. On this basis, this paper develops a composite GIS-based walkability measure (0-1) for Berlin metro area and investigates the association of walkable neighborhood design with ethnic diversity (i.e., Entropy Index). We explore this relationship by applying spatial regression models (i.e., OLS, GWR), while we control the effects of traffic-related air pollution (i.e., NO2), building height, and children density. Our findings suggest that for the total of 447 Berlin neighborhoods which were examined only one out of three had walkability scores greater than 0.5 as well as that community ethnic diversity is negatively related to walkability (β=-0.159, p<0.01).